Immediate Effects of Acupuncture on the Mechanosensitivity of the Median Nerve: An Exploratory Randomised Trial. Issue 3 (June 2018) - Morais, Nuno; Greten, Henry Johannes; Santos, Maria João; Machado, Jorge Pereira
Background: Acupuncture appears to reduce the mechanosensitivity of peripheral nerves in animal models; yet, this possibility has not been demonstrated in humans. Objectives: The main objective of this exploratory trial was to evaluate the immediate effects of acupuncture on the mechanosensitivity of the median nerve, measured by the elbow extension range-of-motion (EE–ROM) at pain onset and maximum tolerance during the upper limb neurodynamic test 1 (ULNT1). Additional objectives were to test the effects of two different points in ULNT1 responses and critically appraise pre-/post-intervention changes for conducting future research. Methods: Thirty-one asymptomatic individuals, randomly assigned to the PC group (n=14) or the LU group (n=17) by the coin flip procedure, underwent acupuncture (leopard spot needling) at PC5 or LU5", respectively. Two-way mixed-model analysis of variance (ANOVA) with time (pre-intervention vs post-intervention) as the within-subject factor and group (PC vs LU) as the between-subject factor, plus time×group interaction, were used to determine the effects of acupuncture therapy on EE–ROM at pain onset and maximum tolerance during ULNT1. Results: At baseline there were no differences between groups (p>0.05). After acupuncture, mean EE–ROM increased 3.1° at pain onset (p=0.029, η 2 p = 0.154) and 5.6° at maximum tolerance (p=0.002, η 2 p = 0.277) with no differences between groups (p>0.05, η 2 p < 0.01). Conclusion: Immediately after acupuncture, the mechanosensitivity of the median nerve appears to be reduced as observed by an increase in EE–ROM during the ULNT1. Further studies are needed to confirm these preliminary findings. Trial Registration Number: NCT02150915; Post-results.